A serological study of bovine leptospirosis in the district of taranaki - Bahaman, A.R.; Marshall, R.B.; Hellstrom, J.S. (Informa UK Limited, 1984)
A cross-sectional serological survey of dairy cattle in Taranaki in 1979–80 indicated that 62% (551/891) of the animals had evidence of Leptospira interrogans serovar hardjo infection as disclosed by the microscopic agglutination test. Titres to Leptospira interrogans serovar pontona were demonstrated in only 4% (23/591) of the animals examined. The high prevalence of hardjo infection is suggestive of an endemic infection whilst the low level to pontona is indicative of sporadic infection. In a detailed examination of 10 herds, 9 revealed high (55%–91%) prevalence of serological reactions to hardjo and the herd profiles of titres, indicated that the animals had become infected at one to two years of age. A field strain of hardjo from cattle as well as the usual laboratory strain (hardjoprajitno) was incorporated in the test but there were no significant differences between the results given by the two antigens.